Cerebellar Superficial Siderosis in Cerebral Amyloid Angiopathy. Issue 2 (February 2022) - Koemans, Emma A.; Voigt, Sabine; Rasing, Ingeborg; van Harten, Thijs W.; Jolink, Wilmar M.T.; Schreuder, Floris H.B.M.; van Zwet, Erik W.; van Buchem, Mark A.; van Osch, Matthias J.P.; Terwindt, Gisela M.; Klijn, Catharina J.M.; van Walderveen, Marianne A.A.; et al.
Abstract : Background and Purpose: Although evidence accumulates that the cerebellum is involved in cerebral amyloid angiopathy (CAA), cerebellar superficial siderosis is not considered to be a disease marker. The objective of this study is to investigate cerebellar superficial siderosis frequency and its relation to hemorrhagic magnetic resonance imaging markers in patients with sporadic and Dutch-type hereditary CAA and patients with deep perforating arteriopathy–related intracerebral hemorrhage. Methods: We recruited patients from 3 prospective 3 Tesla magnetic resonance imaging studies and scored siderosis and hemorrhages. Cerebellar siderosis was identified as hypointense linear signal loss (black) on susceptibility-weighted or T2*-weighted magnetic resonance imaging which follows at least one folia of the cerebellar cortex (including the vermis). Results: We included 50 subjects with Dutch-type hereditary CAA, (mean age 50 years), 45 with sporadic CAA (mean age 72 years), and 43 patients with deep perforating arteriopathy–related intracerebral hemorrhage (mean age 54 years). Cerebellar superficial siderosis was present in 5 out of 50 (10% [95% CI, 2–18]) patients with Dutch-type hereditary CAA, 4/45 (9% [95% CI, 1–17]) patients with sporadic CAA, and 0 out of 43 (0% [95% CI, 0–8]) patients with deep perforating arteriopathy–related intracerebral hemorrhage. Patients with cerebellar superficial siderosis had more supratentorial lobar (median number 9 versus 2, relative risk, 2.9 [95% CI, 2.5–3.4]) and superficial cerebellar macrobleeds (median number 2 versus 0, relative risk, 20.3 [95% CI, 8.6–47.6]) compared with patients without the marker. The frequency of cortical superficial siderosis and superficial cerebellar microbleeds was comparable. Conclusions: We conclude that cerebellar superficial siderosis might be a novel marker for CAA. Abstract : Supplemental Digital Content is available in the text.